Assessment of IS Ideological Threat - Mahfuh Haji Halimi (2019)
On 18 February 2019, Berita Harian published an article on the ideological threat posed by the IS terrorist group (“Penilaian ke atas ancaman ideologi IS”). This is an abridged version of the article which dwells on IS’ propagation of ‘Jihād and Khilāfah’, the impact of its ideological propaganda, and the way forward to counter its threat.